THE RELATIONSHIP BETWEEN CARING, COMFORT, AND PATIENT SATISFACTION IN THE EMERGENCY ROOM, RATU ZALECHA HOSPITAL, SOUTH KALIMANTAN, INDONESIA - Sirajudin Noor; Insana Maria; Agianto Agianto (Belitung Nursing Journal, 2016)
Background: Emergency nursing service system requires the role of nurses who are able to pay attention to the behavior of caring and patient comfort. Caring in an emergency room is an important aspect in lifesaving procedures. It might impact the psychology of patients if nurses are not caring. Caring behavior and comfort given by nurses can also affect to patient satisfaction. Patient satisfaction is considered important as a bridgehead for the treatment of patients. Objective: The purpose of this study is to determine the relationship between caring behavior and comfort with patient satisfaction in the emergency room, Ratu Zalecha Hospital, South Kalimantan, Indonesia. Method: This was an analytic correlational study with cross-sectional approach involved 341 patients in the emergency unit using consecutive sampling. Four questionnaires were used to measure the characteristics of the respondent, the nurse caring behavior, comfort given by the nurses, and patient satisfaction. Data were analyzed using descriptive statistics for respondents’ characteristic, and chi-square to analyze the relationship between variables. Result: There were 285 respondents (92.8%) who received nurses’ caring behaviors were satisfied, and 268 respondents (87.3%) stated that the nurses were able to provide comfort in nursing care in the emergency room. Conclusion: This study revealed that there was a relationship between caring behavior, and comfort with patient satisfaction. It tells that caring and comfort are very important components that influence the satisfaction of patients. Therefore, the role of nurse to provide caring and comfort for the patients in the future should be developed along with the development of science and technology and society's demands.